An exploratory study of organisational factors associated with the effectiveness of companies in the Namibian tertiary industry - Ngwangwama, Matthias Mpareke (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.